Analysis of Carnegie Learnings MATHia Artificial Intelligence Implementation in Mathematics Learning: Perspectives of Prospective Mathematics Teachers and Implications for Schools in Indonesia - Muhadir, Faiha Azimati; Ramadhani, Aulia Rizka; W, Wahyunengsi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to evaluate the use of Carnegie Learning MATHia artificial intelligence in the mathematics learning process from the perspective of prospective mathematics teachers in Indonesia. The method used is a descriptive quantitative approach with an instrument in the form of a closed questionnaire distributed via Google Forms to prospective teachers and students studying mathematics education. The data was processed descriptively to determine the respondents perspectives on the effectiveness, challenges, and impacts of using MATHia. The results showed that most respondents had a favorable view of MATHia, especially in improving conceptual understanding, efficiency in teaching, and student learning independence. The average score of the statements ranged from 3.12 to 4.04. This shows that most respondents see great potential of this technology in supporting a more independent and effective learning process. This study concludes that the success of MATHia integration in mathematics education depends on policy support, teacher readiness, and a clear and comprehensive implementation strategy. These findings benefit teachers, policymakers, and technology developers in increasing the use of AI to improve the quality of mathematics education in Indonesia.